Pendampingan Penguatan Pendidikan Peserta Didik dan Prangtua melalui Program Unggulan Tahfidz Quran, Hizbul Wathan, Silat Tapak Suci di MIS Muhammadiyah Pariaman - Hamzah Irfanda (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Strengthening the education of students and parents through flagship programs such as Tahfidz Quran, Hizbul Wathan, and Silat Tapak Suci is a noble effort that must be present in Islamic education, especially in the era of information disruption 5.0. The strategic role of teachers, parents, and religious leaders is crucial in shaping a generation that is both faithful and virtuous. Education that integrates religious values and local wisdom serves as a foundation for facing the increasingly complex challenges of the modern world. Therefore, the community service team is committed to sharing the knowledge they possess with parents, teacher councils, and students at Madrasah Ibtidaiyah Swasta Muhammadiyah Kota Pariaman. Through this program, it is expected that the understanding and skills in educating children will improve, and the relationship between schools, families, and communities will be strengthened. With proper guidance, it is hoped that future generations will be able to face global challenges while maintaining strong religious and moral principles.